ELASTISITAS HUKUM ISLAM (Studi Konsep Hukum Al-Shaârani Dalam Kitab Al-Mizan Al-Kubro) - Hamzawi, Mochammad Adib (Jurnal al Hikmah, 2016)
The Islamic education convised had absolute truth. But the truth of fiqih as Islamic education aplication concept not ever confessed absolute, the procces of fiqih formulation influenced by approach methode, surrounding and social-culture atmosphere, mujtahid turned up distinction wich implicated to pluralist of Islamic law. Beside it was gleaming activity in the beginning of Islam. But another side the result of vanery ikhtilaf exactly made broked fraternity of religious life. The singular truth claim and primordialisme behavior of people made weak the shariâah shine clamed as salih li kulli zaman wa al-makan. Where is the recite about ikhtilaf needed to look for the solution in ordered the variety became bless and impact and impact of was destruktif for moeslem people. Al-Shaârani by means of his creation al-Mi>zan al-Kubra with explanatoris evaluative character was one of Ulamaâ found the handling ikhtilaf concept. Fiqih in al-Shaârani perspective had to look in elastition a manner two valence that was azimah had tashdi>d character and rukhsoh had takhfif character. In ordered the plurality of fiqih not to negative impact the pluratition of fiqih not to negative impact. Al-Shaârani gave two concept in holding ikhtilaf problem. The first the meaning shariâah in a extensive manner the second the employing Al-Jami wa al-Taufiq method. Finnaly moslem people had to always breadned firmament knowledge about Islmic shariâah. Where as application had to be classifier about situation and condition wich incuded it. By means Islam as Rahmah lilâalamin religion materialized",